Implementasi Program Smart and Health Children di Daerah 3T Papua Selatan Melalui Taman Belajar dengan Tema Sanitasi dan Literasi Berbasis HOTS - Uspayanti, Rezky; Pertiwi, Sri Ananda; Sahruni, Ade Yuni (Jurnal Pengabdian UNDIKMA, 2025)
This community service program aims to enhance students' understanding of sanitation practices and develop literacy and critical thinking skills based on higher-order thinking skills (HOTS) through the Smart and Healthy Children program conducted in the 3T (frontier, outermost, and least developed) regions of South Papua. The activities consisted of five stages: preparation, optimization of sanitation and literacy facilities, teacher training, student habituation, and evaluation. The evaluation instruments used interviews and student learning outcome tests which were then analyzed using descriptive statistics. The results of this community service program showed a significant improvement in students’ understanding across four aspects: the importance of sanitation, sanitation procedures, reading comprehension, and reading analysis. Moreover, positive behavioral changes were observed among students, including regular habits of bathing, hand washing, brushing teeth, using latrines, and trimming nails, all of which were monitored by teachers. The use of an outdoor learning garden also contributed to a more dynamic learning environment. Overall, the program not only successfully enhanced students’ health knowledge but also fostered enthusiasm and engagement in daily literacy activities, demonstrating its effectiveness in developing both sanitation awareness and literacy skills among students in the 3T regions.